Policy Burdens, Accountability, and the Soft Budget Constraint - Lin, Justin Yifu; Tan, Guofu (American Economic Review, 1999)
In a socialist economy, when a state-owned enterprise (SOE) incurs losses, the government often provides it with additional funding, cuts its taxes, and offers other compensations. Coincidentally, the managers of an SOE also expect to receive financial assistance from the state. Such a phenomenon is called the soft budget constraint (SBC), a term coined by Janos Kornai (1986). Kornai attributes many problems in a socialist economy to the existence of the SBC. To achieve successful reform of both the SOE's and socialist economies, it is imperative to eliminate the SBC. However, the SBC phenomenon continues to exist in transitional economies, even after SOE's are privatized (World Bank, 1996 p. 45). There is a large literature on the SBC. Mathias Dewatripont et al. (1996) and Eric Maskin (1996) provide surveys on the recent literature. According to Kornai (1998), there are two types of explanations for the existence of the SBC: the exogenous and endogenous. Explanations of the first type attribute the existence of the SBC to various exogenous reasons, including the paternalism of a socialist state and the government's aims for job creation or for gaining political support (Kornai, 1986). Explanations of the second type view the SBC as an endogenous phenomenon, arising from a time-inconsistency problem (Dewatripont and Maskin, 1995). For an inefficient, uncompleted investment project, the state or creditor may have incentives to refinance the investment because the marginal benefit of refinancing exceeds the marginal cost of abandoning it. Yingyi Qian (1994) attributed the shortage of goods in socialist economies to the SBC based on such a timeinconsistency argument. In this paper, we provide another explanation for the prevalence of the SBC in socialist and transitional economies. We will argue that the SBC is rooted in the state's accountability problem. The traditional Stalinist system was designed to facilitate the establishment of certain strategic SOE's, which were not viable in a market system. To establish the nonviable SOE's, a socialist government distorted the prices of all kinds of inputs and of outputs and used administrative measures to allocate these inputs and outputs according to plans. However, due to information and coordination problems, the state could make wrong decisions regarding investment/production and fail to deliver necessary materials and inputs in time. Consequently, the state, instead of SOE's, was accountable for the failures and needed to allocate additional credits and other assistance to the SOE's in order to complete the investment and production. As such, the SBC arose. After the transition to a market economy, many strategic firms still remain nonviable in a market economy. For strategic purposes, the state needs to support these finns. Moreover, most firms in a transitional economy carry many types of policy burdens, inherited from the pretransition system (Lin et al., 1998). Because the state is accountable for the losses arising from policy burdens, the SBC phenomenon persists. In a market economy, the state's attempts to build nonviable industry and the state's policy burdens on enterprises will also lead to SBC.